Lower for Longer: Neutral Rate in the U.S. Issue Volume 64:Issues 4(2016) (November 2016) - Pescatori, Andrea; Turunen, Jarkko
Abstract We use a semi-structural model to estimate neutral rates in the United States. Our Bayesian estimation incorporates prior information on the output gap and potential output (based on a production function approach) and accounts for unconventional monetary policies using estimates of "shadow" policy rates. Results show a significant trend decline in the neutral real rate post-1990s, driven only in part by a decline in trend growth, whereas other factors (including excess global savings and risk premia) matter. Neutral rates likely turned negative during the global financial crisis and are expected to increase only gradually looking forward.